The Influence of Service Quality and Company Image on Customer Satisfaction and Word of Mouth (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this research is to investigate the relationship among service quality, company image, customer satisfaction, and word of mouth. The population of this study is the parents of students in Avesiena Nature School Malang, East Java, Indonesia, which is 193 people. This study used saturated sample, it means the sample is the same number with the population. In order to examine the relationship both direct and indirect between service quality and company image on word of mouth, this study used path analysis. According to validity and reliability tests, the data that used in this study can be said valid and reliable. Results of this study show that service quality, company image, and customer satisfaction have a significant impact on word of mouth. Indirectly or through customer satisfaction, service quality and company image also have a significant effect. Key words: Service Quality, Company Image, Customer Satisfaction, Word of Mouth